Legal Ambiguity and Its Impact on Community Criminalization in Mining Obstruction Cases: An Inclusive Legal Perspective: Ambiguitas Hukum dan Dampaknya terhadap Kriminalisasi Masyarakat dalam Kasus Penghalangan Pertambangan: Perspektif Hukum yang Inklusif - Sirjon, Lade (Rechtsidee, 2023)
This normative legal research scrutinizes the implications of criminal provisions concerning parties who hinder mining, and critically investigates an inclusive legal perspective on the penalization of such parties. The research, underpinned by a conceptual and statutory approach, identifies that the ambiguous penal provisions can potentially result in criminalizing local communities engaging in activities perceived as obstacles to mining operations. It highlights a critical contradiction between these punitive measures and the principle of affirmative action within prophetic law. The study also exposes a legal obscurity pertaining to the lack of parameters to define acts that hinder or obstruct mining operations, which contributes to the risk of community criminalization around mining sites. The research culminates in suggesting legal and political strategies to address this issue: a judicial review at the Constitutional Court, and hearings and aspirations at the People's Representative Council (DPR) to revise mining criminal law regulations. This study reveals that such interventions are crucial to ensure lex certa, a component of the principle of legality, which can provide legal certainty to affected communities, thus reducing unwarranted community criminalization.Highlights: Legal ambiguity may criminalize local communities. Current punitive measures contradict affirmative action. Judicial review and legislative amendments are necessary for legal certainty. Keywords: Legal Ambiguity, Mining Obstruction, Community Criminalization, Inclusive Legal Perspective, Affirmative Action.